Preliminary design of integrated power and thermal management systems for hybrid electric VTOL aircraft architecture - Kang, Sangkeun; Saias, Chana Anna; Roumeliotis, Ioannis; Broca, Olivier (American Society of Mechanical Engineers (ASME), 2026)
Hybrid and fully electric vertical takeoff and landing (VTOL) aircraft present promising solutions to improve urban traffic congestion but face challenges such as limited power and energy density and stringent thermal constraints, requiring effective thermal management. Optimizing the available onboard electrical energy in hybrid-electric aircraft is crucial, and this can be achieved through the implementation of an effective power management strategy. This paper presents a design methodology for an integrated power and thermal management system (IPTMS) using a parallel hybrid-electric civil tilt-rotor aircraft modeled after XV-15, as a case study. A multidisciplinary optimization platform is developed, integrating IPTMS optimization with rotor aerodynamics, flight dynamics, gas turbine performance, mission analysis, and electric powertrain performance models. The study evaluates both direct air-cooling and liquid-cooling options, incorporating Phase Change Materials (PCMs) for heat storage to identify the most effective thermal management solution. A design space exploration is conducted across various degrees of hybridization (DoH) to assess performance impacts both with and without the integration of the thermal management system (TMS). The results indicate that lower DoH with air-cooling TMS result in energy efficiency and emission improvement, while higher DoH configurations encounter thermal load and payload constraints. For shorter-range, double-leg missions, air-cooling with PCMs proved beneficial, achieving up to 8.76% improvement in energy efficiency and emission reductions of 12.95% for CO2 and 1.66% for NOx. Although electrification optimizes energy use and emissions, conventional aircraft still outperform when the maximum payload constraint is lifted through enhanced payload allocation. This work provides a comprehensive framework for IPTMS design in hybrid-electric VTOL aircraft, balancing power and thermal management for efficient and sustainable operation.
Keywords: 4009 Electronics, Sensors and Digital Hardware; 40 Engineering; 4008 Electrical Engineering; 7 Affordable and Clean Energy; Energy; 4001 Aerospace engineering; 4004 Chemical engineering